Optimization of Jepara Police District Criminal Investigation Child and Women Protection Unit Performance in Handling Child Sexual Abuse to Improve Crime Clearance - Khrisna, Imanuel (Indonesian Journal of Police Studies, 2024)
The increasing reports of children sexual abuse cases in Jepara has not yet been offset with the resolvedcases. This can be seen from the data from 2019 to 2021, where the number of reported cases has increased, but the number of resolved cases has not been increased significantly. In 2020, case reports increased to 31 cases but only 23 cases were solved and 8 cases were pending. In 2021, case reports increased to 27 cases but only 13 cases were solved and 14 cases were pending. This study uses a qualitative research approach with a case study research, which researchers going to the field directly to collect data by conducting interviews, observation and document studies. The data found is then validated with reduced data which is then presented for conclusions. This study uses management theory, organizational resource theory and SWOT analysis theory as well as several concepts related to these problems, namely the concept of Children, Child Sexual Crime and Crime Clearance. The results from the research are that the Criminal Investigation Unit PPA still has some deficiencies in the process of planning, organizing, implementing and supervising because it is not in accordance with the procedures listed in UU no. 11 of 2012 concerning the Juvenile Justice System. In addition, there are factors that are affecting the Jepara Police District Criminal Investigation Bureau Child And Women Protection Unit’s performance in handling Children sexual abuse so that it cannot be carried out optimally.